2016
DOI: 10.1002/ptr.5646
|View full text |Cite
|
Sign up to set email alerts
|

Anti-infective potential ofCitrus bergamiaRisso et Poiteau (bergamot) derivatives: a systematic review

Abstract: Infectious diseases remain among the leading causes of morbidity and mortality worldwide, mainly because of the increase of resistance to chemotherapeutic drugs. Nature is the major source of anti-infective drugs and could represent a font of medicines that may help overcome antibiotic resistance. Recently, the potential antimicrobial effect of certain plant extracts has attracted attention within the scientific community as alternatives to synthetic drugs. Here, we present a systematic review on the anti-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 66 publications
0
35
1
1
Order By: Relevance
“…Thus, different susceptibilities are, probably, imputable to the strains tested, rather than to oils compounds. Our best MIC result (0.625 μL/mL – 0.625 % v/v) is higher than value reported by Cirmi et al (2016) (0.125 % v/v) on a single L. monocytogenes strain.…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, different susceptibilities are, probably, imputable to the strains tested, rather than to oils compounds. Our best MIC result (0.625 μL/mL – 0.625 % v/v) is higher than value reported by Cirmi et al (2016) (0.125 % v/v) on a single L. monocytogenes strain.…”
Section: Discussioncontrasting
confidence: 72%
“…In this context, we have recently shown that BJe has antioxidant properties [235,236] and is able to suppress pro-inflammatory responses in both in vitro [237,238] and in vivo models [239,240]. Interestingly, evidence showing that BJ did not significantly affect the viability of normal human diploid fibroblast WI-38 cells [229], as well as not provoking any apparent sign of systemic toxicity [231], together with its antimicrobial activity [241,242] and favorable safety/efficacy balance [243], reveals the potential of BJe as an anti-cancer remedy, highlighting that it could represent a novel strategic approach in oncology field. …”
Section: Anti-cancer Properties Of Citrus Juices and Extractsmentioning
confidence: 99%
“…Amongst CFs, Citrus bergamia Risso et Poiteau (bergamot) has gained an ever‐increasing attention of the scientific community. It found the most appropriate climate conditions in the southern coasts of the Calabria region (Italy), where it is cultivated primarily for the extraction of the essential oil (BEO) from the peel, exploited mainly in cosmetic industry and in aromatherapy (Mannucci et al, ), as well as studied for its activity as antimicrobial (Cirmi, Bisignano, Mandalari, & Navarra, ) and anti‐proliferative agent (Navarra et al, ). Bergamot juice (BJ) has always been considered a by‐product, yet in the last decade, the beneficial effects of its flavonoid‐rich extract (BJe) have been highlighted by several studies (Cirmi et al, ; Ferlazzo, Cirmi, Calapai, et al, ; Mannucci et al, ).…”
Section: Introductionmentioning
confidence: 99%